ПОЛУЖЕСТКОКРЫЛЫЕ: RIDUVIIDAE, РАСПРОСТРАНЁННЫЕ НА СЕВЕРО-ЗАПАДЕ КАРАКАЛПАКСТАНА - Абдуллаева, Дж.К.; Сапаров, А.Д. (SCIENCE and SOCIETY, 2025)
This article provides a general overview of the fauna of the insect family Reduviidae on the Ustyurt Plateau, located in the northwestern part of Uzbekistan. In total 6 genera, including 10 species of the Reduviidae family, were registered in Uzbekistan (Karakalpakstan). Two species from the family Reduviidae, Reduvius ciliatus (Yakovlev, 1879) and Reduvius personatus (Linnaeus, 1758), were first recorded in the fauna of Uzbekistan.